2013
DOI: 10.1074/jbc.m112.439893
|View full text |Cite|
|
Sign up to set email alerts
|

Matrix Metalloproteinase Mmp-1a Is Dispensable for Normal Growth and Fertility in Mice and Promotes Lung Cancer Progression by Modulating Inflammatory Responses

Abstract: Background: MMP1 is overexpressed in malignant tumors and its levels are associated with poor prognosis. Results: Mice deficient in Mmp-1a, the ortholog of human MMP-1, develop fewer lung carcinomas than controls and show a Th1 anti-inflammatory response. Conclusion: Mmp-1a is a protumoral protease that alters Th1/Th2 cytokine balance. Significance: Mmp1a-deficient mice are a new model for the functional analysis of this metalloproteinase in cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Thus far, Mmp1a expression has been detected in LLC1, urethane-induced lung cancer, B16 melanoma cells, and ovarian and breast cancer xenografts, as discussed previously (Boire et al, 2005; Foley et al, 2012; Fanjul-Fernández et al, 2013). Additionally, Mmp1a expression drives migration and invasion in primary cutaneous melanoma tumors with constitutive BRAF activity from V600E BRAF V600E /p19 ARF −/− mice (Foley et al, 2012).…”
Section: Mmp1a In Other Cancer Modelssupporting
confidence: 54%
See 1 more Smart Citation
“…Thus far, Mmp1a expression has been detected in LLC1, urethane-induced lung cancer, B16 melanoma cells, and ovarian and breast cancer xenografts, as discussed previously (Boire et al, 2005; Foley et al, 2012; Fanjul-Fernández et al, 2013). Additionally, Mmp1a expression drives migration and invasion in primary cutaneous melanoma tumors with constitutive BRAF activity from V600E BRAF V600E /p19 ARF −/− mice (Foley et al, 2012).…”
Section: Mmp1a In Other Cancer Modelssupporting
confidence: 54%
“…Recent studies have directly demonstrated important functional roles for Mmp1a in lung cancer models (Fanjul-Fernández et al, 2013; Foley et al, 2012, 2013). Lewis lung carcinoma (LLC1), a c57BL/6 mouse-derived, non-small cell lung cancer (NSCL) cell line, expresses high levels of Mmp1a protein (Foley et al, 2012).…”
Section: Mmp1a In Lung Cancer Modelsmentioning
confidence: 99%
“…Furthermore, we have provided in this paper experimental proof about the mechanistic role of MMP-25 in NF-kB activation, promoting the ubiquitination of TRAF6 through its direct interaction with the E2 ligase UEV1A. Previous works have described the function of MMPs in different physiological and pathological situations related with immune system and inflammation, such as responses to infectious and autoimmune diseases, cancer progression, and wound healing (14,(34)(35)(36)(37). Although further studies should address the specific biochemical nature of this cross-talk between MMP-25 and NF-kB, this work has described new regulatory functions for this family of metalloproteinases that could be promising for exploring the functions of MMPs on different mechanisms mediated by NF-kB, including those associated with the modulation of inflammation during aging processes (38)(39)(40).…”
Section: Discussionmentioning
confidence: 83%
“…To raise this conclusion, it has been necessary to generate this new strain of mutant mice because the mouse model deficient in MMP-25 (MT6-MMP) was one of the very few in vivo murine models of MMP deficiency that was not yet available. Similar to most MMP-deficient mice (13,14), Mmp25-null mice are fertile and viable and do not exhibit apparent phenotype abnormalities. However, it is remarkable that our studies have unveiled new aspects of the functional relevance of MT6-MMP, demonstrating a critical role for this metalloproteinase in innate immunity through the control of WBCs activation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation